Computer vision, imaging and computer graphics theory and applications : 13th International Joint Conference, VISIGRAPP 2018, Funchal-Madeira, Portugal, January 27-29, 2018, Revised Selected Papers /: 13th International Joint Conference, VISIGRAPP 2018, Funchal-Madeira, Portugal, January 27-29, 2018, Revised Selected Papers. (2019) - Unknown
No abstract available